Biofiltro a base de cáscara del cacao para la depuración de aguas grises domésticas en el sitio la Liza-Membrillo - Loor Párraga, Gema Deyanehira (2023)
The objective of the research was to design a biofilter with cacao shell (Theobroma cacao L.) for the removal of contaminants from domestic gray water at the La Liza site. Three phases were proposed, starting with the application of the rapid participatory diagnosis applied to families belonging to the community to learn about cocoa production, 11 farms were identified where the Nacional and CCN51 varieties are harvested; A monitoring was carried out in the dry and rainy season to know the amount of cocoa shell waste generated in the community, obtaining that in the rainy season the generation of waste is greater than the Nacional variety with an average value of 780.00 kg. . In the second phase, the physicochemical composition of the cocoa shell of both cocoa varieties present in the community was determined; The design of the three biofilters was carried out, which consist of a dimension of 1 m, which were made up of layers of standard filtering material, adding a layer of cocoa flour in three different proportions. Finally, the removal efficiency of the biofilter was determined, evidencing the positive influence of filter 1 (cocoa shell at 20%), demonstrating efficiency levels in the removal of total solids by 38%, COD with 59%, and turbidity. by 20%; presented an 85% incidence of removal of oils and fats, however, the pH presented a significant increase of 37% due to the properties of the cocoa shell.